2011
DOI: 10.1115/1.4004951
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Abradable Coating Removal in Aircraft Engines Through Plastic Constitutive Law

Abstract: In the field of turbomachines, better engine performances are achieved by reducing possible parasitic leakage flows through the closure of the clearance distance between blade tips and surrounding stationary casings and direct structural contact is now considered as part of the normal life of aircraft engines. In order to avoid catastrophic scenarios due to direct tip incursions into a bare metal housing, implementation of abradable coatings has been widely recognized as a robust solution offering several adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(117 citation statements)
references
References 22 publications
3
111
0
3
Order By: Relevance
“…It was shown that a bilinear plastic law could accurately represent the mechanical behavior of abradable material. Consistently, recent numerical developments focused on the modeling of abradable coating through mono-dimensional plastic elements [10] in the context of full 3D blade-tip/abradable coating simulation. Recent applications of this strategy [11] proved promising results in good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It was shown that a bilinear plastic law could accurately represent the mechanical behavior of abradable material. Consistently, recent numerical developments focused on the modeling of abradable coating through mono-dimensional plastic elements [10] in the context of full 3D blade-tip/abradable coating simulation. Recent applications of this strategy [11] proved promising results in good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 98%
“…Most of those developments are only briefly recalled and more information may be found in [10] regarding abradable coating modeling, reduced order model taking into account centrifugal effects as well as the contact algorithm.…”
Section: Solution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interaction phenomena are intrisically non-linear and indeed require dedicated computational tools to overcome the current limitations of commercial softwares such as: (1) the absence of efficient strategies for the modeling of abradable coating removal [2] or, (2) the impossibility to build physically relevant reduced-order models (ROM) of rotating structures subjected to contacts [3]. The physical relevance of rotor reduced-order models is intimately related to the modeling of both centrifugal and gyroscopic effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus of great interest to assess the severity of this phenomenon for other types of compressor such as centrifugal compressors, also named impellers. Several references, both dealing with numerical simulations [3,4,2] and experimental set-ups [5,6,7], may be found on interaction phenomena or rubbing and abradable sealing properties in fan or axial compressors. However, the exploration of interaction phenomena for centrifugal compressors is not yet documented.…”
Section: Introductionmentioning
confidence: 99%